Inhibition of B cell receptor signaling induced by the human adenovirus species D E3/49K protein - Hildenbrand, Andreas; Cramer, Precious; Bertolotti, Milena; Kaiser, Nathalie Sophia; Kläsener, Kathrin; Nickel, Clara Muriel; Reth, Michael; Heim, Albert; Hengel, Hartmut; Burgert, Hans-Gerhard; Ruzsics, Zsolt (Frontiers in Immunology, 2024)
The early transcription unit 3 (E3) of human adenoviruses (HAdVs) encodes several immunoevasins, including the E3/49K protein, which is unique for species D of HAdVs. It is expressed as surface transmembrane protein and shed. E3/49K of HAdV-D64 binds to the protein tyrosine phosphatase surface receptor CD45, thereby modulating activation of T and NK cells. Considering that E3/49K represents the most polymorphic viral protein among species D HAdVs, we demonstrate here that all tested E3/49K orthologs bind to the immunologically important regulator CD45. Thus, this feature is conserved regardless of the pathological associations of the respective HAdV types. However, it appeared that modulation of CD45 is a unique property restricted to HAdVs of species D. Moreover, E3/49K treatment inhibited B cell receptor (BCR) signaling and impaired BCR signal phenotypes. The latter were highly comparable to B cells having defects in the expression of CD45, suggesting E3/49K as a potential tool to investigate CD45 specific functions. In conclusion, we identified B cells as new direct target of E3/49K-mediated immune modulation, representing a novel viral immunosubversive mechanism.